Uma proposta de interconexão de proteções para detecção de ilhamento em sistemas de geração distribuída - Muraro, Matias Rossato (2014)
This work presents a methodology for detecting islanding in distributed generation systems - DG - which use internal combustion engines as primary sources and synchronous generators connected directly to grid. The proposed method considers the characteristics of this type of DG, and is based on the analyses of the injected power and voltage level to disable or enable the under/over frequency protection. The proposed protection scheme considers the frequency as the main electrical signal, and has three stages: the first stage is disabled when power injected oscillations are detected, in the others cases, the stage is enabled; the second stage is normally disabled, it will be enabled when a balanced voltage is detected after a unbalanced voltage condition and the third stage is normally enabled and is used to detect large frequency deviations. The proposed protection was tested over diferentes events, islanding with different load and generation levels, temporary short-circuit and islanding during short-circuit. The results show the efficiency and reliability in detecting islanding, presenting no false detections.